2021
DOI: 10.3390/cancers13123087
|View full text |Cite
|
Sign up to set email alerts
|

Review of PP2A Tumor Biology and Antitumor Effects of PP2A Inhibitor LB100 in the Nervous System

Abstract: Protein phosphatase 2A (PP2A) is a ubiquitous serine/threonine phosphatase implicated in a wide variety of regulatory cellular functions. PP2A is abundant in the mammalian nervous system, and dysregulation of its cellular functions is associated with myriad neurodegenerative disorders. Additionally, PP2A has oncologic implications, recently garnering attention and emerging as a therapeutic target because of the antitumor effects of a potent PP2A inhibitor, LB100. LB100 abrogation of PP2A is believed to exert i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…Recently published data are confirmed that ULK1 is also able to induce PP2A via phosphorylation suggesting a positive feedback loop (i.e., ULK1 -> PP2A -> ULK1) in the control network (see regulatory connections ‘c’ and ‘d’ on Figure 1 ) [ 28 ]. Interestingly, a PP2A-dependent inhibition of mTORC1 has been also observed, which has a negative effect on mTORC1 activity [ 22 , 23 , 35 , 36 , 37 ]. Besides, mTORC1 can inhibit PP2A via phosphorylation [ 24 , 25 , 26 ] generating a mutual antagonism between the two proteins (mTORC1 -| PP2A -| mTORC1) (see regulatory connections ‘e’ and ‘f’ on Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published data are confirmed that ULK1 is also able to induce PP2A via phosphorylation suggesting a positive feedback loop (i.e., ULK1 -> PP2A -> ULK1) in the control network (see regulatory connections ‘c’ and ‘d’ on Figure 1 ) [ 28 ]. Interestingly, a PP2A-dependent inhibition of mTORC1 has been also observed, which has a negative effect on mTORC1 activity [ 22 , 23 , 35 , 36 , 37 ]. Besides, mTORC1 can inhibit PP2A via phosphorylation [ 24 , 25 , 26 ] generating a mutual antagonism between the two proteins (mTORC1 -| PP2A -| mTORC1) (see regulatory connections ‘e’ and ‘f’ on Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, ULK1 enhances PP2A activity via phosphorylation, which creates a positive feedback loop (i.e., ULK1 -> PP2A -> ULK1) [ 28 ]. In addition, a mutual antagonism is observed between mTORC1 kinase and PP2A phosphatase, suggesting another double negative feedback loop in the control network [ 22 , 23 , 24 , 25 , 35 , 36 , 37 ] ( Figure 1 ). Here we explored in the first time the dynamical characteristic of mTORC1-ULK1-PP2A controlled reversible phosphorylation/dephosphorylation upon cellular stress by approaching our analysis from a systems biological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these studies implicate PP2A as an important rheostat for therapeutic response and suggest that the spatial regulation of PP2A activity may lead to distinct phenotypes and unique therapeutic combinations depending on cellular context. In an effort to modify PP2A activity in tumors, three main therapeutic strategies have been explored: preventing cellular inhibitors from binding to PP2A, directly nucleating the PP2A holoenzyme or global inhibition of PP2A (Table 2 ) ( 143 , 144 ).…”
Section: Therapeutic Targeting Of Pp2a In Cancermentioning
confidence: 99%
“…On the other hand, cancers such as glioblastoma show therapeutic efficacy with PP2A catalytic inhibitors, such as LB100, particularly when used in combination with DNA damaging therapeutics ( 122 , 174–177 ). The combination of PP2A and epigenetic inhibitors are currently being explored and may prove effective in malignancies of the nervous system ( 122 , 144 ). In either context (activation or inhibition), PP2A holds great promise as a therapeutic target as more specific compounds are developed (Table 2 ).…”
Section: Therapeutic Targeting Of Pp2a In Cancermentioning
confidence: 99%
“…Previous reviews have examined LB100 adjuvant therapies in adult and pediatric nervous system tumors, including glioblastoma, pheochromocytoma, medulloblastoma, diffuse intrinsic pontine glioma, and neuroblastoma 20 . Others have focused on LB100 treatment in systemic solid tumors, including breast cancer, ovarian carcinoma, hepatocellular carcinoma, pancreatic cancer, and sarcoma 4 .…”
Section: Introductionmentioning
confidence: 99%